Pembentukan karakter siddiq dan amanah melalui program market day di MTS Swasta Sidratul ‘Ulya - Sri Sundari; Mesran; Syariah Hafizhoh; Hasnah Siahaan (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
The purpose of this research is to: (1) To know how the formation of character Siddiq through the Market Day Program that is implemented in the Private MTs Sidratul ‘Ulya. (2) To find out how the creation of character Trust through the Program Market Day that is performed in private MTs sidratul’ Ulya. This research uses a qualitative approach with a type of qualitatively descriptive research. The object of the study is the formation of a crater siddiq and trust in students of Private MTs Sidratul ‘Ulya. The methods of data collection used are interviews, observations, and documentation. Results [research shows that 1) The formation of character siddiq students always given and implanted by the teacher of Private MTs Sidratul 'Ulya Tanjung Morawa. According to the researchers, the formation of the character of Siddiq in students is classified into two categories: customization and uniformity. The practices that students do in the Market Day program with the presence of religious values, students are trained to carry out the values of honesty in the process of sale and purchase up to the report of earnings. The practice makes students accustomed to honesty. 2) The formation of a confidence character is always pursued by the teacher systematically, through the implementation of the Market Day program with the assignment of tasks individually or in groups, implementation in a timely and routine manner. Because the nature of Trust is very important for students and teachers, so that the goal of learning is achieved well. If there is a child who has difficulty forming his character, then the teacher will give special attention and learning to the student.